The impact of CSI-300 stock index futures on the volatility of stock price based on panel data analysis - HE, RUIZHEN (2020)
This paper analyses the change in Chinese stock volatilities after CSI-300 index futures was introduced into the market on 16 April 2010. The investigated period is from 1 August 2006 to 31 December 2013. To study this effect, the panel data evaluation approach is used. This paper uses random effects model, fixed effects model and Hausman test to conduct empirical analysis. The results of empirical analysis are slightly ambiguous. The futures related variable of the change rate of open interest affects the underlying stock volatilities insignificantly, while the variable of trading volume divided by open interest significantly influence them. The coefficients of these two variables under regression indicate that futures trading is positive correlated with the change in stock volatility. However, the overall cash market volatility was still decreasing according to the regression results. This suggests that although the trading on CSI-300 index futures lead more price fluctuations on the underlying cash market, this effect was covered by some other factors. In conclusion, this paper provides possible explanation for this outcome regarding to the Chinese specific financial environment and some suggestions on the improvement and development of Chinese futures market.